Holistic classical interpretation: Analysis of Halal and Haram in Food made from processed fruit from the Qur'an perspective - Putri, Delsi Amelia; Jannah, Miftahul; Jamiah, Khaoiriratal; Akbar, Ali (Journal of Modern Islamic Studies and Civilization, 2023)
Considering the importance of legal clarity regarding halal (permissible) and haram (forbidden) matters in Islamic law, especially concerning food consumption, and the growing popularity of processed fruit products among the community, this research becomes crucial to discuss. This holds significant relevance in the lives of Muslim individuals. While the Quran provides clear guidance on what halal and haram are, a holistic understanding of classical Quranic exegesis can offer a deeper and more relevant insight into the context of modern life. The analysis focuses on the processing of fruits, considering the materials and methods used. Evaluation is conducted based on the halal criteria outlined in classical exegesis. This research employs a literature review and Quranic exegesis analysis method to scrutinize the concepts of halal and haram in processed fruits from the perspective of the Quran, utilizing a holistic approach to classical exegesis. The expected outcome of this study is to contribute to Islamic literature and practice by integrating classical exegesis concepts into the understanding of halal and haram in processed fruit products.